When the Project Is Writing The Rules: Temporary Use and Aporias in the Planning Law - Marzot, Nicola (Sens public)

(untitled) (Département des littératures de langue française, 2024)
After a decade of design explorations and reflections, meanwhile uses are widely accepted by the international community as a successful multidisciplinary approach to deal with the post-financial crisis main consequences. Among them, can be counted the increasing offer of waiting lands and vacant buildings and the search of unconventional agents of transformation to claim any abandoned space. What is still missing, however, is the acknowledgment that the impact of the phenomenon and its diffused quality, mostly interstitial, is giving us an unprecedented possibility to reconsider the definition and management of the city’s form. In that perspective, since the 60s of the last century, the planning activity succeeded to claim a total control over the territorial development, expanding the role of the calculating thinking to a limitless unprecedented perspective. Therefore, architecture was progressively reduced to a stylistic exercise to confirm ex-post political decision already taken out of any previous spatial experimentation. This paper aims to demonstrate that meanwhile uses can contribute to limit the hubris of the contemporary planning and, beyond that, to imagine new urban configurations for the existing city. The ex-railroad freight Ravone in Bologna, Italy, is the proposed testing ground, which seems to confirm this vision.